Studi Efisiensi Perbankan Syariah di Kota Lhokseumawe dan Aceh Utara - Iskandar Iskandar (AL-TAHRIR, 2012)
The development of Islamic banking in Aceh should have get more attention because its existence is not only as complement of thenational banking system, but also as an attempt to fill the Islamic Shari ’a with the Islamic financial institutions. The issue becomes important to investigate since the efficiency of banking institutions urgently need to this performance. Thus, in this study, the efficiency of Islamic banking will be viewed from two aspects: Firstly, the ability of the bank in generating output, in this case the low cost of financing. Secondly, efficiency can also be observed by looking at the bank’s performance in minimizing the risk of financing. This study concluded that the main difficulty of Aceh Islamic banks is not the lack of cheap enough money so that the efficiency becomes less when it is compared with the required cost. However, the annual report shows that the assets of Islamic banks have developed positively and good. Likewise, the ratio of Non Performing Ratio (NPF) of Islamic banks is efficient. The study recommends enhancing the cheap fundraising (al-wadi <’ah) to increase the economic growth in the northern coastal area of Aceh.